Temporal Characteristics of Energetic Magnetospheric Electron Precipitation as Observed During Long‐Term Balloon Observations. Issue 11 (28th October 2020) - Bazilevskaya, G. A.; Kalinin, M. S.; Krainev, M. B.; Makhmutov, V. S.; Stozhkov, Y. I.; Svirzhevskaya, A. K.; Svirzhevsky, N. S.; Gvozdevsky, B. B.
Abstract: The paper summarizes the properties of precipitation of magnetospheric electrons with energy above several hundred keV recorded by observing X‐ray bremsstrahlung in the polar stratosphere above the Murmansk region, Russia, in 1961–2019. Precipitation occurrence rate demonstrates a clear dependence on the solar activity with a maximum at the decay phase of the 11‐year solar cycle, similarly to the variability in occurrences of the high‐speed solar wind streams (HSSWS). The energetic electron precipitation (EEP) event series is often initiated by a moderate geomagnetic storm caused by a HSSWS and continues during geomagnetic storm recovery. EEP demonstrates the seasonal rate variation with the maxima in occurrence rate around the spring and the autumn solstices and correlates with fluences of relativistic electrons in the outer radiation belt. For 59 years, 589 events of precipitation were observed. Analysis of the long‐term time series revealed a growing trend in the rate of precipitation occurrence, especially in the 1990s to 2000s that is not properly explained yet. Plain Language Summary: Since the beginning of the 1960s, the group from Lebedev Physical Institute watches the precipitation of energetic electrons from the outer radiation belt to the atmosphere. The precipitation reflects the condition in the interplanetary space and in the magnetosphere, that is, it is governed by solar activity. In the 1990s, solar activity started weakening: the maximum annual mean of sunspot number decreased from 233 in Solar Cycle 21 to 116 in Cycle 24. But the occurrence rate of precipitation increased, which has not found an explanation yet. Key Points: Balloon observations allow recording precipitation of magnetospheric electrons via bremsstrahlung in the atmosphere Since 1961 till 2019, 589 electron precipitation events were observed in the Murmansk region An unexpected increase of precipitation occurrence rate was found in the 1990s to 2000s